Bi2S3-reduced graphene oxide composite for gaseous radioiodine capture and its immobilization within glass composite material. (May 2021) - Zou, Hao; Guo, Jiabin; Song, Mianxin; Yi, Facheng; Wang, Xiaoqiang; Pan, Ning; Li, Hailong; Li, Weimin; Bian, Liang
Abstract: A potential method of disposing iodine-129 in off-gas produced from spent fuel reprocessing was discussed in this paper. Firstly, the Bi2 S3 -reduced graphene oxide (RGO) composite was successfully synthesized via a solvothermal method. Secondly, the iodine adsorption process of the Bi2 S3 -RGO composite was discussed, showing that the iodine was captured by the composite mainly in the form of BiI3 and little in the form of I2 . The iodine capturing capacity of the composite is about 1042.8 mg/g, which is much higher than that of other reported inorganic materials. Finally, the iodine immobilization process of the Bi2 S3 -RGO composite that captured iodine was investigated, indicating that the iodine could be solidified by the glass composite material (GCM) in the forms of BiOI and Bi5 O7 I. Graphical abstract: Image 1 Highlights: The Bi2 S3 -RGO composite was first applied to dispose gaseous radioiodine. The capturing capacity of the composite was calculated about 1042.8 mg/g. The proposed mechanism of the iodine adsorption and immobilization reaction in the system was investigated.